2010 35th IEEE Photovoltaic Specialists Conference 2010
DOI: 10.1109/pvsc.2010.5614267
|View full text |Cite
|
Sign up to set email alerts
|

The etchback selective emitter technology and its application to multicrystalline silicon

Abstract: We have developed a simple and industrially applicable selective emitter cell process using only one diffusion step and an emitter etchback to create the high sheet resistance emitter [1, 2]. The process generates a deeper doping profile with a lower surface phosphorous concentration than a directly diffused emitter with the same sheet resistance. This results in an extremely low emitter saturation current j0E even at a moderate sheet resistance of 60-80 Ω/. The highest independently confirmed cell efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The time needed for an effective co-gettering could be noticeably reduced compared to plain BDG. [36] Obviously, if the etch back method [37] is used to form the emitter, it is possible to use high dopant concentrations and, in principal, separately optimize the gettering efficiency and the doping profile.…”
Section: Resultsmentioning
confidence: 99%
“…The time needed for an effective co-gettering could be noticeably reduced compared to plain BDG. [36] Obviously, if the etch back method [37] is used to form the emitter, it is possible to use high dopant concentrations and, in principal, separately optimize the gettering efficiency and the doping profile.…”
Section: Resultsmentioning
confidence: 99%
“…There are various techniques and applications to form selective emitter structures [48]. Double-diffusion with masking [49,50], selective diffusion barrier process [51], oxide masking process and etch back [45,52], implantation process [53] are among these techniques. Depending on the technique, need of laser ablation, additional steps like masking, repeated diffusions, etch back processes are among the drawbacks of such techniques.…”
Section: Selectively Screen-printing and Single Diffusion Processmentioning
confidence: 99%
“…In the case of mono-Si wafer solar cells, Book et al [18] were unable to maintain the integrity of pyramidal shape after an etch-back as portions of the tips of the pyramids were etched during their acidic etch-back process. On the other hand, Basu et al [7,[19][20][21] showed that the 'SERIS etch' was able to maintain the integrity of surface pyramids even for deep etch-backs.…”
Section: As-diffused Emittersmentioning
confidence: 99%
“…All the processes mentioned up to now only enable relatively shallow homogeneous emitter etch-backs of up to 10 Ω/sq. The main problem associated with deeper etch-backs is that they are typically not very conformal and thus reflectance from the emitter surface increases after a deeper etch-back [18]. Consequently the potential of the etch-back processes is limited.…”
Section: Introductionmentioning
confidence: 99%